Hotel and lodging management : an introduction - Stutts, Alan T (John Wiley & Sons, 2015)
"Hotel and Lodging Management, Second Edition prepares readers to succeed as managers in the hotel and lodging industry, while developing a solid foundation for a long and successful career. This comprehensive resource combines detailed presentations of each department in a hotel or lodging establishment along with a close examination of organizational structure and the interdependent relationship among departments."--Jacket.